Penurunan Biaya Persediaan dengan Metode Joint Replenishment Multi Item Single Supplier - Donny Montreano (JIEMS (Journal of Industrial Engineering and Management Systems), 2018)
The purpose of this research is to describe multi-item ordering method (Goyal, 1974) by providing a complete information of algorithm on each step. The journal itself doesn’t contain sufficient information on its example, and there is an error on a simple calculation. We observed a pulp manufacturer as raw material for making paper, tissue, printing paper and non-printing paper. There were 3 materials that purchased from a supplier and had been overstock in 2016. The materials will be examined by this method in order to reduce overstock. The results are shows that there is about 91% of the total inventory cost discrepancy between that period of total inventory cost and these methods of total inventory cost. This cost saving can be used for other investigation, for example, Indonesian Ritel Obligation or stock exchange.